2014
DOI: 10.1093/jxb/eru175
|View full text |Cite
|
Sign up to set email alerts
|

Fusion, rupture, and degeneration: the fate of in vivo-labelled PSVs in developing barley endosperm*

Abstract: SummaryThe article provides in vivo imaging data on the morphological changes in the endomembrane architecture of developing barley seeds, focussing on the fate of protein storage vacuoles along endosperm development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 46 publications
4
46
0
Order By: Relevance
“…Additionally, the seed weight between the stages are significantly different except the stage between 6 and 10 DAP ( Supplementary Fig. S2e) These results are in line with the previously published microscopic data where the most dramatic endomembrane rearrangements could be observed between 8 and 12 DAP 13 .…”
Section: Multivariate Statistics Unravel Proteome Reorganization Acrosupporting
confidence: 91%
See 3 more Smart Citations
“…Additionally, the seed weight between the stages are significantly different except the stage between 6 and 10 DAP ( Supplementary Fig. S2e) These results are in line with the previously published microscopic data where the most dramatic endomembrane rearrangements could be observed between 8 and 12 DAP 13 .…”
Section: Multivariate Statistics Unravel Proteome Reorganization Acrosupporting
confidence: 91%
“…3a-c). PBs are identified in the bright field as small spherical structures as recently published 13,15,16 . Interestingly, a faint actin signal was observed at the plasma membrane at ≥20 DAP, whereas the signal of tubulin at the plasma membrane was strong at 6 DAP but was reduced at 12 and ≥20 DAP ( Fig.…”
Section: Development Phase I Contains Proteins Of High Abundance Assomentioning
confidence: 85%
See 2 more Smart Citations
“…Generated hydrogen peroxide might serve as a signal introducing the programmed cell death and subsequently kernel desiccation (Onda et al, 2009). More recently, Ibl et al (2014) suggested that both the membrane shrinkage and degeneration of PB occurred before PB development were completed in barley endosperm cells. The synthesis of vast amounts of disulfide-rich storage proteins during grain-filling (Figure 4E and G) might be accompanied by the production of hydrogen peroxide in ER, resulting in the peroxidation of membrane lipids under normal conditions (Sattler et al, 2006; Onda et al, 2009).…”
Section: Discussionmentioning
confidence: 99%